IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH STORY MAPPING - Arif Budiman; Regina Regina; Yanti Sri Rezeki (Universitas Tanjungpura, 2019)
Abstract This article aims to describe the use of story mapping in improve Students’ reading comprehension of narrative text, in order to solve the students’ problem in reading comprehension of narrative text. Interviewing the English teacher, the writer found that the students get big difficulties to identify the specific information of the story. This research was conducted through a Classroom Action Research in two cycles, where each cycle consisted of four stages, they are planning, acting, observing, and reflecting. The participants of this research were the English teacher and 26 students in class VIIIB. The writer used measurement and observation techniques to collect the data. The writer elaborated the result of observation checklist, field note and students’ mean score in order to get the research findings. The result showed that students were able to identify the specific information of the story with good reading comprehension. The mean score of students’ reading comprehension was enhanced in each cycle. In the first cycle, the students’ mean score was 73.26, it increased to 77.88 in the second cycle,and reached the KKM as well. In conclusion, story mapping improved the students’ reading comprehension of narrative text. Keywords: Improve, Narrative Text , Students, Reading, Story Mapping